The new corporate social responsibility: a call for sustainability in business education. (4th December 2009) - Sherman, Peter; Hansen, Jan
Researchers have studied the role of social responsibility in organisations for decades. Despite this extensive work, the teaching of corporate social responsibility in the classroom across the business curriculum remains somewhat limited. In order for educators in business to catch up with corporations who are increasingly focusing on issues and stakeholders beyond the bottom line, there must be an increased and integrative focal point on sustainability. This paper makes a call an increased focus on sustainability across business disciplines and makes recommendations on how they can be implemented.